Fruit and pulp production of the African grape Lannea microcarpa Engl. & K. Krause from dry and humid Sudanian in Northern Benin, West Africa - GOUDEGNON, Eude Oré Adédiran; Gouwakinnou, Gérard Nounagnon; HOUESSOU, Laurent; Oumorou, Madjidou (My University, 2016)
Lannea microcarpa, an Anacardiaceae species associated to crops in farmlands in West Africa is a multipurpose tree used in traditional medicine, human and animal feeding in Sudanian zone of Benin. This study aimed at evaluating L. microcarpafruits and pulp production in dry and humid Sudanian zone. Fruit and pulp production and dendrometric variables were collected on 21 and 27 trees. Data were analysed using two independents samples t-test and Pearson correlation to find out variation in production and relation between variables. Trees in dry Sudanian zone showed the largest crown. The number of fruit, fruit mass and pulp mass were highest in dry Sudanian zone. Also, trees with high diameter at 1.30 m above the ground had produced low number of grapes and fruit per grape. Pruning and debarking did not affect the fruit and pulp mass. In humid Sudanian zone, tree crown could be used as indicator of number of fruit per grape on one hand and on the other hand the number of tertiary branches could be used for fruit and pulp produced. Debarking is positively correlate with fruit and pulp production. This study highlighted that in northern Benin, dry Sudanian zone could be preferable for L. microcarpa fruit and pulp production. The variations observed between zones deserve to be investigated.
Keywords: Lannea microcarpa production; Humid and dry Sudanian zone; Benin; West Africa